Propuesta para la optimización de la red inalámbrica de área Local (WLAN) en las oficinas centrales de la corporación de Supermercados unidos mediante la mejora en la configuración de los puntos de acceso (ACCESS POINTS). - Calvo-Román, Jorge Eduardo (Instituto Tecnológico de Costa Rica, 2003)
the wireless mobile communication field. We saw today how the use of wireless devices is rising everyday specially the use of celular phones. This is because of the versatibility it has in the job activities or any other daily activity, in keeping close the person with his/her family or co-workers at any time and any place over the world. This facility offered by wireless communications in mobile phones, is also taking force in the field of data networks, either in local areas or long distances. The same conception mencioned latetly in mobility, has impressed the enterprises which expect more advantages in comparison with tradicional wired networks. Some of the advantages they saw in this technology is the fact that they offer equipment mobility, faster installation, roaming by the entire building without loosing internet conexion and the easy administration it provides. Wireless LAN are a complement of tradicional wired networks, specially when you are doing big industrial solutions were it requires that the stations be located at the source. Previously the WLAN solutions weren’t promoted because they didn’t have a regulatory standard, but it was solved with the appearence of IEEE 802.11 standard for wireless LAN.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería Electrónica, 2003.
Keywords: Ganancia; Patrones; Polarización; Parámetros; Seguridad; Usuarios